Strategic management : Indian experience - Roy, Dilip; National Seminar on Strategic Management (1996 : Burdwān, India) (New Delhi : Gyan Pub. House, 1997)
Collection of articles presented at the National Seminar on Strategic Management, organized by Dept. of Business Administration, Burdwan U., on Feb. 3-4, 1996.
Includes bibliographical references and index.
Keywords: Strategic planning -- India -- Congresses; Business planning -- India -- Congresses; Industrial management -- India -- Congresses; India -- Economic policy -- Congresses